2022
DOI: 10.1126/sciadv.abm9436
|View full text |Cite
|
Sign up to set email alerts
|

Designing polymeric membranes with coordination chemistry for high-precision ion separations

Abstract: State-of-the-art polymeric membranes are unable to perform the high-precision ion separations needed for technologies essential to a circular economy and clean energy future. Coordinative interactions are a mechanism to increase sorption of a target species into a membrane, but the effects of these interactions on membrane permeability and selectivity are poorly understood. We use a multilayered polymer membrane to assess how ion-membrane binding energies affect membrane permeability of similarly sized cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 52 publications
(81 reference statements)
0
60
0
Order By: Relevance
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , b TEM-void fraction was calculated as the ratio between the area of the voids in the PA layer and the total area of the PA layer, where the areas were measured by the software Image pro plus based on the TEM micrographs. c TEM-apparent thickness was measured as the overall thickness of the crumpled nanovoid-containing PA layer using Image pro plus based on the TEM micrographs. d SEM-surface coverage was calculated as the ratio between the projected area of the exterior PA layer and the projected area of the total PA layer, where the areas were measured by Image pro plus based on the SEM micrographs. e AFM-RMS (root-mean-square roughness), AFM-average height, and AFM-surface area ratio were obtained by the AFM tests. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , b TEM-void fraction was calculated as the ratio between the area of the voids in the PA layer and the total area of the PA layer, where the areas were measured by the software Image pro plus based on the TEM micrographs. c TEM-apparent thickness was measured as the overall thickness of the crumpled nanovoid-containing PA layer using Image pro plus based on the TEM micrographs. d SEM-surface coverage was calculated as the ratio between the projected area of the exterior PA layer and the projected area of the total PA layer, where the areas were measured by Image pro plus based on the SEM micrographs. e AFM-RMS (root-mean-square roughness), AFM-average height, and AFM-surface area ratio were obtained by the AFM tests. …”
Section: Resultsmentioning
confidence: 99%
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…Such interactions require a low activation energy to take place ( E a , Figure ), leading to observed initial high retention followed by a breakthrough phenomenon. Furthermore, it was shown that species (e.g., metal ions) with higher binding to the membrane sites can more selectively pass through and permeate, whereas the permeation of weaker binding species (hence hindered adsorption) is significantly reduced . Notably, MPs with a higher binding energy to the NF membrane show a higher adsorbed mass, and hence, breakthrough can gradually take place.…”
Section: Resultsmentioning
confidence: 99%
“…DFT can help inform the interaction energy between two or more molecular fragments. For membranes, DFT calculations can be applied to investigate the effect of the binding energy between aqueous ions and functional groups in a polymeric membrane on ion transport . Other examples include DFT-derived reaction energies and barriers to construct reaction networks in complex chemical processes, such as polymerization …”
Section: Simulation Methods Across Various Scalesmentioning
confidence: 99%